2020
DOI: 10.1051/e3sconf/202018304005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pomological and biochemicalquality of Moroccan almond native genetic resources for conservation of biodiversity

Abstract: The edible and tasty almond {Prunus amygdalus [syn. P. dulcis (Mill.) D.A.Webb]} kernel is not anymore the main reason for its production and uses, other properties related to its by-products, especially the sweet edible almond oil, which is mainly used as a salad dressing or as an ingredient in a highly appreciated Moroccan almond-based recipes. The studied almond populations are derived from seedling, the trees of these plantations are very heterogeneous in terms of vigor and flowering time and are facing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The total sugar content (TS) of the almond flour fractions vary between 9.73% and 17.15%, and there is a significant difference between the almond-cake flour fractions and the wheat flour SWF (TS: 84.84%). The results are similar to those of Rabadán et al (2017) and where they reported that the TS values of their almond cake flours ranged between 14.97 -27.64% and 16.73-17.42%, respectively [5,6].…”
Section: Carbohydrate Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The total sugar content (TS) of the almond flour fractions vary between 9.73% and 17.15%, and there is a significant difference between the almond-cake flour fractions and the wheat flour SWF (TS: 84.84%). The results are similar to those of Rabadán et al (2017) and where they reported that the TS values of their almond cake flours ranged between 14.97 -27.64% and 16.73-17.42%, respectively [5,6].…”
Section: Carbohydrate Analysissupporting
confidence: 91%
“…Almond oil is known for its rich natural antioxidants (tocopherols (vitamin E), polyphenols), which makes it an excellent edible oil, but it is widely used in cosmetics [1][2][3] due to its profitability. Almond oil extraction generates by-products, almond oil extraction residues known as almond meal or almond cake, which is rich in proteins, fibres and minerals [4][5][6], which can be valued.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of covered area, almonds rank second after olives production in Morocco. The special climate characteristics and environmental conditions in north and south Morocco ensure the huge genetic variability of almond cultivars explaining the vigorous production and the high quality of Moroccan almonds [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the production, recent plantings have incorporated more intensive cultural practices as well as new cultivars originating from Spain and France [15,16]. To avoid genetic erosion of "Beldi" almond ecotypes and the loss of interesting genotypes, several recent researches are focused on a serious identification of "local cultivars" based on seedling selections which represented the germplasm of the region and where a traditional culture system was evolved that minimized inputs of labour, fertilizers, and uses of additional irrigations during dry periods [17]. Moreover, many problems like the attack of the bark beetle "Scolytus Amygdali," an important pest that belongs to the Scolytidae family, which is considered as one of the most destructive insect pests in coniferous and fruit trees in both temperate and tropical climates, could occur [18].…”
Section: Introductionmentioning
confidence: 99%